2020
DOI: 10.21640/ns.v12i24.2081
|View full text |Cite
|
Sign up to set email alerts
|

Análisis in vitro de la acumulación de metales pesados en plantas de la familia Asparagaceae tolerantes a la baja disponibilidad de agua

Abstract: Introducción: La familia Asparagaceae incluye varios géneros adaptados para sobrevivir a altas temperaturas y con baja disponibilidad de agua. Entre éstos destacan Agave, Beaucarnea, Dasylirion, Nolina y Yucca. México cuenta con una gran biodiversidad de estos grupos vegetales, así como con una tradición ancestral en cuanto a su uso. Los sistemas de propagación in vitro son eficientes para la producción de estas plantas, y además pueden ser usados para llevar a cabo diversos tipos de estudios. Entre es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…The scientific community has indicated that agave has a high agro-ecological value, given its ability to retain soil, infiltrate moisture (TORRES-GARCÍA et al, 2019), and it's potential to phytostabilize and remediate contaminated soils (PERALES et al, 2020). Also, the decrease in the cultivated area of maguey and the erosion of knowledge about its use (AGUILAR et al, 2014;ÁLVAREZ-DUARTE et al, 2018) lead to the loss of its genetic variability, which puts it in danger of extinction to various endemic species (MONJA-MIO et al, 2019) ecologically, economically and culturally relevant in rural areas of Mexico.…”
Section: General Aspects and Uses Of Agaves The Maguey Pulquero In Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific community has indicated that agave has a high agro-ecological value, given its ability to retain soil, infiltrate moisture (TORRES-GARCÍA et al, 2019), and it's potential to phytostabilize and remediate contaminated soils (PERALES et al, 2020). Also, the decrease in the cultivated area of maguey and the erosion of knowledge about its use (AGUILAR et al, 2014;ÁLVAREZ-DUARTE et al, 2018) lead to the loss of its genetic variability, which puts it in danger of extinction to various endemic species (MONJA-MIO et al, 2019) ecologically, economically and culturally relevant in rural areas of Mexico.…”
Section: General Aspects and Uses Of Agaves The Maguey Pulquero In Mexicomentioning
confidence: 99%
“…Agave salmiana can also contribute to remediating contaminated soils (PERALES et al, 2020) and the aguamiel can be used as a substrate in the production of nematodes for biocontrol of pests (ISLAS-LÓPEZ et al, 2005).…”
Section: And Nutritional Valuementioning
confidence: 99%
“…Estos elementos no fueron transferidos a las hojas, como se observa en el TF <1, As 0,3 y Pb 0,05 (Tabla III). De acuerdo con Perales et al (2020), un valor TF mayor de 1 indica una eficiente translocación del metal a brotes, por lo que la planta puede usarse con fines de fitoextracción. Si por el contrario, dicho valor es menor de 1, la translocación del metal es baja, por lo que este es retenido principalmente en las raíces pudiendo ser utilizado para fitoestabilización, por lo que vetiver actuó como fitoestabilizadora.…”
Section: Concentración De As Y Pb En Hojas Y Raízunclassified